If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -4) + -6 = -6(-2x + 4) + -6x Reorder the terms: 2(-4 + x) + -6 = -6(-2x + 4) + -6x (-4 * 2 + x * 2) + -6 = -6(-2x + 4) + -6x (-8 + 2x) + -6 = -6(-2x + 4) + -6x Reorder the terms: -8 + -6 + 2x = -6(-2x + 4) + -6x Combine like terms: -8 + -6 = -14 -14 + 2x = -6(-2x + 4) + -6x Reorder the terms: -14 + 2x = -6(4 + -2x) + -6x -14 + 2x = (4 * -6 + -2x * -6) + -6x -14 + 2x = (-24 + 12x) + -6x Combine like terms: 12x + -6x = 6x -14 + 2x = -24 + 6x Solving -14 + 2x = -24 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -14 + 2x + -6x = -24 + 6x + -6x Combine like terms: 2x + -6x = -4x -14 + -4x = -24 + 6x + -6x Combine like terms: 6x + -6x = 0 -14 + -4x = -24 + 0 -14 + -4x = -24 Add '14' to each side of the equation. -14 + 14 + -4x = -24 + 14 Combine like terms: -14 + 14 = 0 0 + -4x = -24 + 14 -4x = -24 + 14 Combine like terms: -24 + 14 = -10 -4x = -10 Divide each side by '-4'. x = 2.5 Simplifying x = 2.5
| 6r+5=55 | | k+3=6+k | | 30+(.0825*30)+(15%*30)= | | 6(y+2)=-2(8y-7)+6y | | -26+26=-15p-10p | | 11x-4=5x+9 | | x*12=-2 | | X+3(4)=48 | | 3x+10=3x+4+1 | | 2(x-1)-3x=8 | | 8-2x=2x-5x | | 1x+3(4)=48 | | 9(-10)+160= | | -6h+2=-46 | | x+7=-3+3x | | .60x+.30(90)=.50(x+90) | | 6=18b | | 3x+15=12b-3b | | x*-5=10 | | 16t^2-128+400=0 | | 2a+24-3a=5a | | 8p-4=7p-2 | | n^2-34n-251=0 | | t^2-8+25=0 | | 1-m=1-m | | 16.28+8=100 | | -4n+2=-13-7n | | x^7-5x+6=0 | | 13x+23y=-5 | | -6+4p=5p-4 | | -3+2x-9=9 | | -10(3+2)-7= |